(untitled) (Conference Zone, 2022)
The goals and objectives of the psychology of children with retarded development are to arm defectologists and oligophrenopedagogues with knowledge about the mental characteristics of this category of children. In order to properly organize the education and correction of children with retarded development, knowledge about the characteristics of these children is very necessary.